Control de spodoptera frugiperda en asparagus officinalis l.cv. uc 157 f1 aplicando bacillus thuringiensis var. kurstaki e insecticidas en huancaquito alto, La Libertad. - Ventura Guanilo, Marco Antonio (2016)
The present working investigation: Control of Spodoptera frugiperda in Asparagus officinalis L.cv. UC 157 F1 applying Bacillus thuringiensis var. kurstaki and insecticides in Huancaquito Alto - La Libertad it was developed during November and December, 2012. The treatments which were used are: Treatment 1 (B. thuringiensis var. Kurstaki + abamectin + Sulphur), Treatment 2 (B. thuringiensis var. Kurstaki + abamectin + Methomyl), Treatment 3 (B. thuringiensis var. Kurstaki + abamectin); which were applied in a way mechanized trough the sprinkling method .5 evaluations were realized, the first evaluation was realized before the application to know the initial population of larvae, the following control evaluations were realized each 4 days distancing the last one for 6 days to observe if there was some variations into the percentage’s control. These evaluations were realized in four points at random of every block of 1.94 m2. From the information obtained it was calculated the larvae percentage’s control for every treatment and then the test of hypothesis was applied between the treatments for every date of evaluation. The results obtained in this investigation have showed that the control of larvae of the stadium first and second of Spodoptera frugiperda was equally effective with B. thuringiensis var. kurstaki + abamectin alone and with sulphur, on the other hand the control of larvae from the third to fourth and of the total of larvae was more effective B. thuringiensis var. kurstaki + abamectin with sulphur.